2013
DOI: 10.1016/j.jcin.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Implications of Newly Revealed, Asymptomatic Abnormal Ankle-Brachial Index in Patients With Significant Coronary Artery Disease

Abstract: The prevalence of newly revealed abnormal, asymptomatic ABI among patients who have significant CAD on coronary angiography was 15.9%. The presence of abnormal ABI was associated with a higher incidence of adverse clinical outcomes over 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 46 publications
10
49
0
6
Order By: Relevance
“…In our study, 20 of 133 patients with CAD (15%) were found to have PAD by ankle-brachial index test. This prevalence of PAD was similar to that reported by Lee et al 18 (385 of 2424 patients with CAD [16%]). Blann et al 12 reported sEng levels to be high in 26 patients with PAD.…”
Section: Saita Et Al Soluble Endoglin Levels In Cad 51supporting
confidence: 91%
“…In our study, 20 of 133 patients with CAD (15%) were found to have PAD by ankle-brachial index test. This prevalence of PAD was similar to that reported by Lee et al 18 (385 of 2424 patients with CAD [16%]). Blann et al 12 reported sEng levels to be high in 26 patients with PAD.…”
Section: Saita Et Al Soluble Endoglin Levels In Cad 51supporting
confidence: 91%
“…2 In patients who underwent diagnostic coronary angiography, an abnormal ABI (≥0.9, ≥1.4) was associated with a significantly higher risk of 3-year composite death, MI and stroke (HR 2.40) compared with a normal ABI. 12 However, some studies have reported inconsistent results with respect to high ABI patients. 13, 15 In the present study, a low ABI was associated with a significantly higher risk of MACE (HR 2.35, 95% CI 1.73-3.17, P<0.0001).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Патологический уровень ЛПИ может отражать не только явные патоло-гические изменения периферических артерий, но так-же их начальные изменения, которые могут оказать влия-ние на развитие сердечно-сосудистых заболеваний (ССЗ) [9,10]. В последние годы стали обращать внимание на тот факт, что оценка ЛПИ может иметь прогностическое значение в различных когортах обследованных [11], не только в эпидемиологических исследованиях, но и у па-циентов с наличием ССЗ [12]. Недавно опубликованы исследования по прогностическому значению ЛПИ у больных ОНМК [13], однако до сих пор такие иссле-дования проводили в зарубежных странах, отече-ственные исследования ЛПИ при ОНМК только стали появляться, и касаются только отдельных клинических вопросов данной тематики [14].…”
Section: Annual Prognosis After Stroke: Role Of Ankle-brachial Index unclassified